The Moderating Role of Cooperation and Job Satisfaction in the Wanghong Industry: The Impact of Technological Integration on Power Dynamics and Creative Labor Management - Guo, Qinghao; Rungsrisawat, Somdech (Journal of Posthumanism, 2025)
With the advent of the digital age, the Wanghong industry, as an emerging digital cultural industry, is profoundly changing the operation mode and power structure of traditional creative work. Technological integration plays an important role in promoting industrial innovation and improving efficiency, but its impact on the management of creative work and power dynamics has not been fully studied. This paper reveals how technology enhances creators’ decision-making capabilities and optimizes resource allocation by analyzing the role of technological integration in task allocation, feedback mechanisms, and creator decision-making, thereby changing the power structure between creators and platforms and among creators. The study also explores how collaboration and job satisfaction, as moderating variables, influence the role of technological integration in creative labor management and power dynamics in different social and organizational contexts.